New-Onset Atrial Fibrillation Is a Red Flag to Microvascular Free Tissue Transfer Failure in Head and Neck Cancer Patients - Tsai, Chia-Hsuan; Chen, Yu-Jen; Lin, Yu-Chih; Liu, Yao-Chang; Kao, Huang-Kai; Mao, Shih-Hsuan (Journal of Reconstructive Microsurgery, 2024)
Background Postoperative new-onset atrial fibrillation (AF) has been shown to be associated with increased surgical morbidity and mortality following cancer ablation surgery. However, evidence of new-onset AF's impact on surgical outcomes in head and neck cancer patients undergoing tumor ablation and microvascular free tissue transfer remains scarce. This study aims to evaluate the association between AF and surgical outcomes in these patients.Methods We enrolled head and neck cancer patients who underwent tumor ablation reconstructed with microvascular free tissue transfer from the National Health Insurance Research Database (NHIRD). Patients were grouped into the following: (1) without AF, (2) new-onset AF, and (3) preexisting AF. The groups were matched by propensity score based on age, gender, cancer stage, and comorbidities. The primary outcome was postoperative complications, whereas all-cause mortality was the secondary outcome.Results In total, 26,817 patients were included in this study. After matching, we identified 2,176 (79.24%) patients without AF, 285 (10.37%) with preexisting AF, and 285 (10.37%) with new-onset AF. Our results demonstrated that the free flap failure rate was twofold escalated in patients with new-onset AF (9.8%) compared to those without AF (5.4%) or preexisting AF (5.3%; p = 0.01). However, we did not identify significant differences among other postoperative complications across groups. Additionally, we found that the risk of all-cause mortality was significantly elevated in patients with preexisting AF (p < 0.001) compared to those without AF or new-onset AF.Conclusion Our study demonstrated that new-onset AF is associated with an increased risk of flap failure and could serve as a predictor. On the other hand, all-cause mortality in patients with preexisting AF was significantly elevated. Close postoperative monitoring in patients with new-onset and preexisting AF is crucial to identify any potential adverse effects.
Keywords: new-onset atrial fibrillation; preexisting atrial fibrillation; head and neck cancer; microvascular free tissue transfer; flap failure